Rock Magnetism of Late Cretaceous to Middle Eocene Strata in the Lesser Himalaya, Western Nepal: Inferences Regarding the Paleoenvironment - Khatri, Dhan Bahadur; Zhang, Weilin; Fang, Xiaomin; Meng, Qingquan; Zhang, Tao; Zhang, Dawen; Paudayal, Khum N. (Frontiers in Earth Science, 2021)
The growth of the southern piedmont of the Himalayan boundary and its depositional setting has changed since uplift of the Himalaya due to continental Indian-Eurasian collision, which has resulted in variation in magnetic minerals in marine- and terrestrial-facies sediments. In this paper, we utilize rock magnetism data from the late Cretaceous to middle Eocene strata, including the Amile and Bhainskati formations from the Lesser Himalaya (western Nepal), to understand the mechanism controlling magnetic susceptibility (χ). The active tectonics strongly influenced SIRM, HIRM, and hysteresis loops, forming both low-coercivity minerals in sediments with low χ from the terrestrial facies (zones I, IIIA, and V) and high-coercivity minerals in the sediments with high χ from the marine facies (zones II, IIIB and IV). Thermomagnetic κ-T curves and frequency-dependent χ (χfd%) values show that sediments with low χ and high χ carry magnetite with coarse non-superparamagnetic (SP) grains and hematite with SP grains, respectively. Comparing the χ data with the lithologic, sedimentary environments, geomorphic features, and sea level data, we propose that low χ values were mainly produced by an increase in terrigenous detrital influx during the regression period of the Tethys Sea, while high χ values formed in marine sediments, which prompted the appearance of ferromagnetic-antiferromagnetic and paramagnetic minerals during the transgression of the Tethys Sea.